LAND USE CHANGE MODELING ABOUT THE ARRANGEMENT OF THE MANAGEMENT BLOCK BUKIT BARISAN GREAT FOREST PARK, NORTH SUMATRA - Fendi Pangihutan Siadari; Zulkifli Nasution; Agus Purwoko (SEAN Institute, 2023)
Bukit Barisan Great Forest Park (THRBB) is designated as the third TAHURA in Indonesia. TAHURA functions as a source of genetics and germplasm, erosion control, information and research center, education and conservation work, recreation and tourism services. Currently, the THRBB area is experiencing many land use changes that are not by the THRBB management block plan. Land use change modeling using the Land Change Modeler (LCM) instrument was carried out to predict land use change patterns by selecting a Multi-Layer Perceptron (MLP) to evaluate several variables that influence land use change. This research aims to analyze changes in land use in 2011-2018, factors influencing changes, predictions for 2033 and develop land use directions in the THRBB area. The results of the analysis show that during the 2011-2018 period, primary forest land decreased by 710 ha (2.19%), secondary forest by 1,185 ha (43.94%), and shrubs by 139 ha (7.58%). The decrease in forest land area was followed by an increase in open land area by 448 ha (59.74%) and dry land agriculture by 1,586 ha (57.46%). The pattern of land change in the THRBB area is from forest land to bushland, open land and dry land agriculture. The most significant driving factor for land use change is distance from roads. The prediction results for land cover in 2033 show that the area of primary forest will be 30,156 ha, secondary forest 1,236 ha, shrubs 2,833 ha, open land 1,375 ha and dry land agriculture 4,074 ha. The direction of land use policy in the THRBB area is forest restoration policy, increasing protection and security activities and law enforcement.